Housing spaces in Europe: a comparative analysis of standards in nine European Countries. (30th September 2020) - Raffo, M; Appolloni, L; D'Alessandro, D
Abstract: Introduction: In recent years, Public Health devoted a growing interest to housing conditions. In particular, housing dimensions and functional characteristics are relevant, mainly considering population ageing and disability. Aim of the study is to compare housing standards of some European countries to analyse their ability to satisfy new population needs. Methodology: The dwellings dimensional standards of 9 European countries (Sweden, UK, Denmark, The Netherlands, France, Germany, Portugal, Spain and Italy) are compared. From the websites of the official channels of the various countries the regulations have been downloaded. The standards have been compared. Results: A wide variability in the dimensions of room among the standards is observed (e.g. single room: from 9 sqm in Italy, to 7 sqm in France, to the absence of any limit in UK, Germany - Hesse and Denmark). Italian and French regulations define housing dimension considering the room use (eg. bed or living room) and the number of people. The Swedish regulation provides performance requirements and functional indications but does not specify the minimum dimensions of habitable rooms. The rooms' minimum height varies between the standards. In Italy and Portugal, the minimum height of the ceiling is intended to be 2.70 m, while in the other nations the minimum heights vary from 2.60 m in the Netherlands to no limit in UK. Conclusions: A diverse approach among European Countries is observed: from a market-oriented logic (e.g., UK), in which minimum dimensions are not defined, to a prescriptive one (Italy), to a functionality-oriented (the Netherlands). The regulations of some Countries are health-oriented especially for most fragile social classes, since, defining larger dimensional standard, they reduce the risk of overcrowding, indoor air pollution and mental distress. However, considering the health, social, environmental and economic trends, many of these standards should be revised. Key messages: Optimal housing standards promote the health and well-being of occupants. Healthy housing, healthy people.